Anion exchange type covalent organic framework material (AECOFs)-based separation medium and preparation and application thereof
By designing and synthesizing anion exchange-type covalent organic framework materials (AECOFs), the efficient separation of natural products is achieved by ion exchange, and the problems of low purity and complex operation in the prior art are solved, and high purity and efficient separation of natural products are achieved.
Patent Information
- Application Number
- CN202410818650.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-06-24
- Publication Date
- 2025-02-25
AI Technical Summary
The existing natural product separation and purification technology has problems such as low purity, complex operation, high cost and low selectivity, making it difficult to obtain high-purity natural products.
Design and synthesize anion exchange covalent organic framework materials (AECOFs) to achieve efficient separation of natural products through ion exchange. The specific method includes introducing functional units with ion exchange function into the COFs structure, synthesizing by solvothermal method, and separating natural products through adsorption and elution processes.
It realizes efficient separation of natural products, with a purity of up to 99%, is easy to operate, has low processing cost, and is recyclable to maintain high efficiency and economicality.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation and application of novel separation medium materials, specifically, prepares anion exchange covalent organic framework materials (AECOFs) by direct method or doping strategy, and utilizes the ion exchange performance of this type of separation medium for separation and purification of natural products. Background Art
[0002] Natural products are diverse, referring to the components or metabolites of animals, plant extracts, insects, marine organisms and microorganisms, as well as many endogenous chemical components in humans and animals, collectively referred to as natural products. They mainly include proteins, peptides, amino acids, nucleic acids, various enzymes, monosaccharides, oligosaccharides, polysaccharides, glycoproteins, resins, colloids, lignin, vitamins, fats, oils, waxes, alkaloids, volatile oils, flavonoids, glycosides, terpenes, phenylpropanoids, organic acids, phenols, quinones, lactones, steroid compounds, tannic acids, antibiotics and other naturally occurring chemical components. In addition to the diversity of sources and structures, a high diversity of biological activities is also a major feature of this library. According to the currently reported activity information, the natural products in the library cover more than 1,000 receptors, more than 500 targets and nearly 100 signal pathways, involving many research fields such as anti-cancer, anti-inflammatory, anti-diabetic, anti-hypertensive, antibacterial, analgesic, antiviral, and anti-Alzheimer's disease.
[0003] Natural products have great application prospects in the field of medicine and health. However, in the research, production, supply and clinical use of drugs, the purity of drugs must be guaranteed to ensure the effectiveness and safety of drugs. Impurities in drugs are the main factor affecting purity. If the drugs contain impurities exceeding the limit, it is possible to change the physical and chemical constants, change the appearance and properties, and affect the stability of the drugs; the increase in impurities also makes the drug content significantly lower or the activity lower, and the toxic side effects significantly increase. Therefore, it is of great significance to obtain high-purity natural products, but it also faces huge challenges. Regardless of the source of natural products, the material components in the system are extremely complex. Taking the natural products in microorganisms as an example, in order to obtain natural products in microorganisms, it is necessary to crush the microorganisms and try to obtain natural products that meet the purity requirements from the complex system. In such systems, the content of active ingredients in natural products is usually very low and difficult to enrich. At the same time, the system is very complex, with large and small molecules, organic and inorganic substances coexisting, especially the existence of isomers and chiral enantiomers with similar structures, which makes separation and purification difficult. In addition, the active ingredients of many natural products have poor stability, are sensitive to heat, and are easily oxidized, hydrolyzed, and racemized. Therefore, it is of great significance to develop mild, convenient, and efficient separation and purification methods.
[0004] At present, the commonly used natural product separation and purification technologies include extraction, resin adsorption, solid phase extraction, chromatography, etc. Among them, the product obtained by extraction has very low purity, and the later separation is difficult, which is not suitable for industrial application; macroporous resin has certain toxicity in terms of its raw materials, and has certain pollution to the separated compounds. The macroporous resin used in pharmaceutical separation has high requirements, so its application has certain limitations. For solid phase extraction and chromatography, the key is the selection and preparation of separation medium. It has been reported that molecular imprinting materials are used for the separation of natural products, but the preparation of molecular imprinting is complex and costly, and there are certain limitations in the research on the recognition mechanism of target molecules and action sites and the specific structure of polymers. General separation and purification methods can only obtain crude extracts, and it is difficult to obtain pure products of single components. In order to obtain active ingredients with higher purity, the currently widely used strategy is to combine various chromatographic separation technologies and repeated recrystallization operations, which has the disadvantages of cumbersome operation, long separation cycle, low efficiency, large consumption of solvents and separation materials, and low selectivity. Starting from the structure and physicochemical properties of plant natural products, it is of great significance to design and develop new separation media and separation systems in a targeted manner. Therefore, it is very necessary to develop a designable separation medium with high adsorption capacity, good specificity and good biocompatibility.
[0005] COFs are a new type of crystalline porous material formed by organic compound monomers connected by covalent bonds. They have the advantages of adjustable structure, regular pores, large specific surface area, low density, high stability, and high biocompatibility. They are widely used in many fields such as catalysis, sensing, energy storage, drug delivery, separation, and functional device manufacturing. Especially in some difficult separation and purification fields, such as gas separation, isomer separation, and enantiomer separation, they are widely studied. The structural designability of COFs is its most significant feature. Various functions can be given to it by modifying the structure; in terms of separation and purification, the high specific surface area gives it a high processing capacity; high stability can extend the service life of the material and reduce costs. In summary, it is promising to develop new separation media with natural products as the separation target by utilizing the structural characteristics and advantages of COFs.
[0006] Most natural products have complex structures with abundant polar groups (amino, carboxyl, hydroxyl, etc.) and conjugated structures (double bonds, triple bonds, aromatic rings, etc.) provide abundant action sites for adsorption and separation. Starting from the structural characteristics of natural products and combining the structural advantages of materials such as COFs, through rational design, various polar groups can be modified in the COFs structure or different charges can be given to the materials. At the same time, COFs have a very high specific surface area and periodic pore structure. Therefore, for natural products with different structures, COFs can be used to capture natural products through various forces such as electrostatic interactions, π-π interactions, and hydrophobic interactions, and finally achieve purification and separation. We have developed a new type of medium for separation and purification of natural products based on COFs materials, which has the advantages of simple operation, strong processing capacity, high stability, and high overall use efficiency. Summary of the invention
[0007] In view of the defects of traditional natural product separation and purification methods, the present invention takes glycyrrhetinic acid synthesized by microbial fermentation as the research object, designs and synthesizes a series of covalent organic framework materials (AECOFs) with anion exchange properties, and uses the above-mentioned AECOFs to achieve efficient separation of glycyrrhetinic acid (purity>99%) mainly through ion exchange.
[0008] On the one hand, the present invention provides a doping method for synthesizing ion exchange COFs, characterized in that the COFs are obtained by reacting monomers containing aldehyde groups, amino groups, hydrazide groups, acetonitrile groups, and anhydride groups in the structure, and functional units with ion exchange function are introduced during the reaction.
[0009] Specifically, the present invention provides a method for synthesizing anionic covalent organic framework materials (AECOFs), characterized in that the covalent organic framework materials are covalent organic framework materials connected by vinyl, imide, imine, azine, keto-enol, hydrazone, β-ketoamine or triazine, and are specifically synthesized by the following steps: COFs are synthesized by solvothermal method. Add organic monomer 1 and organic monomer 2 to a glass tube, add a reaction solvent to the glass tube, and vortex mix; dissolve a certain proportion of functional monomer 3 in an aqueous solution of a catalyst, add it to the glass tube in liquid form, and place the glass tube in a high-temperature oven or oil bath for reaction. After the reaction is completed, the final product is obtained by cleaning and activation.
[0010] Preferably, the structure of the organic monomer is Figure 1 As shown, the monomer type is di-linked, tri-linked or tetra-linked, and X, Y, and M in the figure are any one of aldehyde, amino, hydrazide, acetonitrile, and anhydride groups.
[0011] Preferably, the organic monomer 1 is a monomer containing an aldehyde functional group. The monomer containing an aldehyde functional group is terephthalaldehyde, 4,4'-biphenyldicarboxaldehyde, 1,4-di(4-formylphenyl)benzene, 1,3,5-tribenzaldehyde (TFp), 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,6-dihydroxy-1,3,5-benzenetricarboxaldehyde, trialdehyde phloroglucinol (Tp), 1,3,5-tri(p-formylphenyl)benzene (TFPB), 2,4,6-tri(4-formylphenyl)-1,3,5-triazine (TFPT), 4,4',4''-[benzene-1,3,5-triyltri(acetylene-2,1-diyl)]tribenzaldehyde (TFEPB), 4,4',4''-(benzene-1,3,5-tri(acetylene-2,1-diyl))-tri(salicylaldehyde) , (2,4,6-tris-(4-formyl-biphenyl-4-yl)-1,3,5-triazine (TFBPT), tetrakis(4-formylphenyl)methane, 4,4',4'',4"'-silanetetraethyltetrabenzaldehyde, tetrakis-(4-formylphenyl)ethylene, 1,3,5,7-tetraformyladamantane, 1,3,5,7-tetrakis(4-benzaldehyde)-adamantane; the monomer containing the aldehyde functional group can be optionally substituted by a substituent, and the substituent is selected from any one or more of -H, -OH, -NH2, -CN, -NO2, -OCH3, -SO3H, -CH3, -COOH, -COOCH3, -F, -Cl, -Br, -I. More preferably, the organic monomer 1 is 1,3,5-triformaldehyde (TFp) and 1,3,5-tris(p-formylphenyl)benzene (TFPB).
[0012] Preferably, the organic monomer 2 is a monomer containing an amino group or a hydrazide functional group. Further preferably, the monomer containing an amino functional group is hydrazine hydrate, p-phenylenediamine, benzidine, 1,3,5-triphenylamine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT), 4,4',4''-[benzene-1,3,5-triyltris(acetylene-2,1-diyl)]triphenylamine (TAEPB), 4',4''',4'''''-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)) (TABPB), 2,4,6-tris-(4-aminobiphenyl-4-yl)-1,3,5-triazine (TABPT), tetrakis(4-aminophenyl)methane, 4,4',4'' ,4"'-silanetetraethyltetraphenylamine, tetrakis-(4-aminophenyl)ethylene, 1,3,5,7-tetraaminoadamantane, 1,3,5,7-tetrakis(4-anilino)-adamantane; the monomer containing the amino functional group may be optionally substituted by a substituent, and the substituent is selected from any one or more of -H, -OH, -NH2, -CN, -NO2, -OCH3, -SO3H, -CH3, -COOH, -COOCH3, -F, -Cl, -Br, -I; the monomer containing the hydrazide functional group is optionally R-substituted terephthaloyl hydrazide; the R is , or When multiple substitutions are present, each R is independently selected from the above structures. More preferably, the organic monomer 2 is 2,5-bis(but-3-ene-1-oxy)terephthaloylhydrazide.
[0013] Preferably, organic monomer 3 is a monomer having an ion exchange functional group in the side chain. Further preferably, the monomer replaces the substituent with any one or more of sulfonic acid (-SO3H), phosphoric acid (-PO3H2), carboxylic acid (COOH), phenolic hydroxyl (-OH), primary amine (-NH2), secondary amine (-NHCH3), tertiary amine [N-(CH3)2] and quaternary amine [-N(CH3)2] groups on the basis of organic monomer 2. Further preferably, organic monomer 3 is 2-(2,5-di(hydrazinecarbonyl)phenoxy)-N,N,N-trimethylethane-1-ammonium bromide.
[0014] Preferably, the catalyst is a compound containing carboxylic acid, anhydride, imidazole, or hydroxyl functional group. Further preferably, the catalyst is any one or more of acetic acid, scandium trifluoromethanesulfonate, benzoic anhydride, 4-trifluoromethylbenzoic anhydride, phenylacetic anhydride, acetic anhydride, trifluoroacetic anhydride, benzoic acid, 4-fluorobenzoic acid, 4-bromobenzoic acid, propionic acid, aromatic acid, imidazole, benzimidazole, or phenol, and further preferably, the catalyst used is acetic acid.
[0015] Preferably, the reaction solvent is any one or more of methanol, ethanol, acetonitrile, mesitylene, o-dichlorobenzene, 1,4-dioxane, n-butanol, acetone, N,N-dimethylformamide, dimethyl sulfoxide, toluene, acetone, and tetrahydrofuran. Further preferably, the reaction solvent used is any combination of mesitylene and 1,4-dioxane, mesitylene and n-butanol, and o-dichlorobenzene and n-butanol. Even more preferably, the reaction solvent is a mixed solvent of mesitylene and n-butanol.
[0016] Preferably, the reaction solvent ratio is mesitylene: n-butanol = 1:0-0:1, further preferably, the ratio is 8:2-2:8, and the most preferred ratio is 1:1.
[0017] Preferably, the ratio of monomer 3 to monomer 2 is 0:1-1:0, more preferably 2:8-8:2, and most preferably 1:1.
[0018] Preferably, the reaction temperature is 30°C-200°C, more preferably 60°C-150°C, most preferably 120°C.
[0019] Preferably, the molar ratio of the aldehyde functional group to the amino or hydrazide functional group contained in the monomers of the reaction system is 1:2-2:1, and more preferably the ratio is 1:1.
[0020] Preferably, the initial concentration of each monomer in the reaction system is 0.001-0.05 mol / L, more preferably 0.002-0.01 mol / L.
[0021] Preferably, the concentration of the acetic acid catalyst is 1-18 mol / L, more preferably 3-9 mol / L.
[0022] Preferably, the concentration of the acetic acid catalyst in the reaction system is 0.01-1 mol / L, more preferably 0.1-0.5 mol / L.
[0023] Preferably, the synthesis reaction time of the covalent organic framework material is 12 h-120 h, more preferably 48 h-96 h, and most preferably 72 h.
[0024] Preferably, the covalent organic framework material includes but is not limited to AECOF-42-B0, AECOF-42-B50, and AECOF-42-B100. The specific structure is shown in Figure 2 .
[0025] Preferably, the solvent used for washing and activating the product is an organic solvent and an aqueous solution having good solubility for the monomer, more preferably acetone, N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, acetonitrile, water, and most preferably tetrahydrofuran.
[0026] More specifically, the present invention provides a method for synthesizing an ion exchange covalent organic framework material, characterized in that a monomer with an ion exchange group is introduced into the reaction, and a product is obtained by a solvothermal method from the monomer reaction, comprising the following steps: 1) Add organic monomer 1 and organic monomer 2 into a glass tube, add a reaction solvent into the glass tube, and vortex mix; 2) dissolving a certain proportion of monomer 3 in an aqueous solution of the catalyst, adding the monomer 3 in liquid form into a glass tube, and vortexing to mix well; 3) Place the glass tube in a high temperature oven or oil bath for reaction; 4) After the reaction is completed, the final product is obtained by cleaning and activation.
[0027] On the other hand, the present invention provides a method for adsorbing and separating glycyrrhetinic acid using anion exchange covalent organic framework materials, characterized in that the adsorption is carried out under weak alkaline conditions and elution is carried out under conditions of higher ionic strength, thereby achieving efficient adsorption and separation of glycyrrhetinic acid. Compared with the existing main extraction methods, resin adsorption methods, solid phase extraction methods, chromatography separation methods, etc., its advantages are: 1) Anion exchange COFs have low density, high specific surface area and high porosity, and large adsorption capacity; 2) Simple operation and low processing cost, only simple adsorption and desorption under aqueous conditions are required to complete the separation and purification of glycyrrhetinic acid in the fermentation broth. 3) Anion exchange COFs have an adjustable pore structure. For natural products with different structures, the pore size and pore environment of the material can be customized to achieve accurate and efficient separation of natural products. It is specifically operated through the following steps: Dissolve glycyrrhetinic acid in an organic solvent, dilute the glycyrrhetinic acid solution with a weak alkaline solution, add AECOFs to a glass bottle containing the above solution, place it on a shaker for adsorption, take points at regular intervals, and calculate the adsorption amount of glycyrrhetinic acid at each time point by testing the absorbance value of the supernatant at 248nm. After the adsorption is completed, filter to separate the AECOFs, add them back to the glass bottle, add a high concentration or high ionic strength solution to the bottle for elution, and calculate the amount of eluted glycyrrhetinic acid.
[0028] After elution is complete, the material is collected by filtration and added back into the glass bottle, to which a salt solution is added for regeneration for subsequent reuse.
[0029] Preferably, the AECOFs are covalent organic framework materials connected by vinyl, imide, imine, azine, keto-enol, hydrazone, β-ketoamine or triazine, more preferably by imine or hydrazone, and more preferably by hydrazone.
[0030] Preferably, the organic solvent used to dissolve glycyrrhetinic acid is ethanol, methanol, acetonitrile, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, more preferably methanol and ethanol, and more preferably ethanol.
[0031] Preferably, the weak alkaline solution is aqueous ammonia, sodium bicarbonate, potassium bicarbonate, sodium acetate, potassium acetate, more preferably sodium bicarbonate and potassium bicarbonate, most preferably sodium bicarbonate.
[0032] Preferably, the high concentration or high ionic strength solution is sodium carbonate solution, potassium carbonate solution, sodium chloride solution, potassium chloride solution, sodium bromide solution, potassium bromide solution, sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, further preferred are sodium carbonate solution, potassium carbonate solution, sodium hydroxide solution and potassium hydroxide solution, most preferred are sodium carbonate solution and potassium carbonate solution.
[0033] Preferably, the salt solution for regeneration is sodium chloride, sodium bromide, potassium chloride, potassium bromide, more preferably sodium bromide and potassium bromide.
[0034] Preferably, the concentration of glycyrrhetinic acid in the organic solvent is 100 μg / mL-1000 μg / mL, more preferably 20 μg / mL-200 μg / mL.
[0035] Preferably, the concentration of the weak base solution is 0.1 mmol-10 mmol, more preferably 0.5 mmol-5 mmol.
[0036] Preferably, the final concentration of glycyrrhetinic acid after dilution with the weak alkaline solution is 5 μg / mL-100 μg / mL, more preferably 20 μg / mL-50 μg / mL.
[0037] Preferably, the concentration of the high concentration or high ionic strength solution is 5 mmol-200 mmol, more preferably 10 mmol-50 mmol.
[0038] Preferably, the concentration of the regeneration salt solution is 0.5 mmol-50 mmol, more preferably 5 mmol-20 mmol.
[0039] Preferably, the adsorption time is 5 min-2 h, more preferably 10 min-30 min.
[0040] Furthermore, the adsorption capacity of glycyrrhizic acid by AECOFs was 40 μg / mg-120 μg / mg.
[0041] Preferably, the desorption time is 1 min-1 h, more preferably 5 min-20 min.
[0042] Furthermore, the single desorption rate of glycyrrhizic acid is 40%-90%.
[0043] Preferably, the regeneration time is 5 min-2 h, more preferably 10 min-30 min.
[0044] Furthermore, the performance of AECOFs can be maintained at more than 80% of the initial level after being reused 10 times.
[0045] On the other hand, the present invention provides a practical use of the AECOFs for separating and purifying natural products from fermentation broth, characterized in that, after simple adsorption, elution and regeneration treatment in the process, high-purity natural products can be separated from the fermentation broth, and the material can be recycled for a long time. The whole process is simple to operate and energy-efficient. It is specifically operated by the following steps: first, the crude fermentation broth is pretreated, and the specific steps are: extracting the crude fermentation broth with an organic solvent and water, collecting the organic phase, removing the solvent and dissolving the residue in an organic solvent miscible with water, adding an alkaline solution to the above solution, filtering to remove the precipitated solid impurities, collecting the filtrate and removing the solvent, and re-dissolving the residue in an organic solvent miscible with water for standby use. The pretreated fermentation broth is diluted with a weak alkaline solution, AECOFs is added to a glass bottle containing the above solution and placed on a shaker for adsorption. After the adsorption is completed, the AECOFs are separated by filtration and added back to the glass bottle. A high concentration or high ionic strength solution is added to the bottle for elution. After the elution is completed, the material is filtered and collected and added back to the glass bottle. A salt solution is added to the glass bottle for regeneration for subsequent reuse.
[0046] Preferably, the natural product in the fermentation broth may be, but is not limited to, any one of glycyrrhetinic acid, glycyrrhizic acid, oleanolic acid and ursolic acid.
[0047] Preferably, the organic solvent used for extraction is ethyl acetate, dichloromethane, chloroform, n-hexane, petroleum ether, more preferably ethyl acetate and dichloromethane.
[0048] Preferably, the organic solvent miscible with water for dissolving the residue is methanol, ethanol, tetrahydrofuran, acetonitrile, N,N-dimethylformamide, dimethyl sulfoxide, and more preferably methanol and ethanol.
[0049] Preferably, the alkaline solution added to the water-miscible organic solvent is sodium carbonate solution, potassium carbonate solution, sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, and more preferably sodium carbonate solution or potassium carbonate solution.
[0050] Preferably, the weak alkaline solution is aqueous ammonia, sodium bicarbonate, potassium bicarbonate, sodium acetate, potassium acetate, more preferably sodium bicarbonate and potassium bicarbonate, most preferably sodium bicarbonate.
[0051] Preferably, the high concentration or high ionic strength solution is sodium carbonate solution, potassium carbonate solution, sodium chloride solution, potassium chloride solution, sodium bromide solution, potassium bromide solution, sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, further preferred are sodium carbonate solution, potassium carbonate solution, sodium hydroxide solution and potassium hydroxide solution, most preferred are sodium carbonate solution and potassium carbonate solution.
[0052] Preferably, the salt solution for regeneration is sodium chloride, sodium bromide, potassium chloride, potassium bromide, more preferably sodium bromide and potassium bromide.
[0053] Preferably, the concentration of the natural product in the organic solvent is 100 μg / mL-1000 μg / mL, more preferably 20 μg / mL-200 μg / mL.
[0054] Preferably, the concentration of the alkali solution added to the water-miscible organic solvent is 10 mmol-500 mmol, more preferably 20 mmol-100 mmol.
[0055] Preferably, the concentration of the weak base solution is 0.1 mmol-10 mmol, more preferably 0.5 mmol-5 mmol.
[0056] Preferably, the final concentration of the natural product after dilution with the weak base solution is 5 μg / mL-100 μg / mL, more preferably 20 μg / mL-50 μg / mL.
[0057] Preferably, the concentration of the high concentration or high ionic strength solution is 5 mmol-200 mmol, more preferably 10 mmol-50 mmol.
[0058] Preferably, the concentration of the regeneration salt solution is 0.5 mmol-50 mmol, more preferably 5 mmol-20 mmol.
[0059] Preferably, the adsorption time is 5 min-2 h, more preferably 10 min-30 min.
[0060] Furthermore, the adsorption capacity of natural products in the pretreated fermentation broth by AECOFs was 40 μg / mg-120 μg / mg.
[0061] Preferably, the desorption time is 1 min-1 h, more preferably 5 min-20 min.
[0062] Furthermore, the single desorption rate of glycyrrhetinic acid is 40%-90%, and the purity of the natural product is above 99%.
[0063] Preferably, the regeneration time is 5 min-2 h, more preferably 10 min-30 min.
[0064] Description of the drawings.
[0065] Figure 1 : Monomer structure used to synthesize COFs.
[0066] Figure 2 : Schematic diagram of the structure of AECOF-42-B0, AECOF-42-B50, and AECOF-42-B100.
[0067] Figure 3 : Powder diffraction results of AECOF-42-B with different doping amounts.
[0068] Figure 4 : FT-IR results of AECOF-42-B with different doping amounts.
[0069] Figure 5 : Nitrogen adsorption and pore size distribution results of AECOF-42-B with different doping amounts.
[0070] Figure 6 : Transmission electron microscopy (TEM) images of AECOF-42-B with different doping amounts.
[0071] Figure 7 : Scanning electron microscope (SEM) images of AECOF-42-B with different doping amounts.
[0072] Figure 8 : The adsorption results of glycyrrhetinic acid by AECOF-42-B50 in different types and concentrations of alkaline solutions.
[0073] Fig. 9 : Adsorption results of glycyrrhetinic acid by AECOF-42-B with different doping amounts in 1 mM NaHCO3 solution.
[0074] Fig.10 : The adsorption results of glycyrrhetinic acid by AECOF-42-B50 under different pH conditions.
[0075] Fig.11 : Adsorption results of glycyrrhetinic acid by different types of ion exchange resins.
[0076] Fig.12 : Desorption results of GA@AECOF-42-B50 in different solutions.
[0077] Fig.13 : Adsorption results of glycyrrhetinic acid with different initial concentrations by AECOF-42-B50.
[0078] Fig.14 : AECOF-42-B50 cyclic adsorption-desorption results.
[0079] Fig.15 : HPLC purity results of samples after pretreatment of fermentation broth with Na2CO3 solutions of different concentrations.
[0080] Fig.16 : HPLC results of glycyrrhetinic acid in fermentation broth pretreated by AECOF-42-B50 adsorption. DETAILED DESCRIPTION Unless otherwise specified in the context of this application, the technical terms and abbreviations used in this application have the conventional meanings known to those skilled in the art; unless otherwise specified, the raw materials used in the following examples are all commercially available. The natural product fermentation broth was provided by Beijing Institute of Technology; the monomer trimesic acid used to synthesize COFs was purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.; and the organic reagents acetonitrile, methanol, ethanol, tetrahydrofuran, etc. were purchased from Tianjin Bohai Chemical Reagent Co., Ltd.
[0082] According to the synthesis of the biocomposite material mentioned in the present invention, the characterization tests of various properties, the catalytic activity detection and the stability test, the specific implementation methods are as follows. The following examples are only used to further explain and invent the present invention, and should not be regarded as limiting the scope of the present invention. The present invention will only be limited by the claims.
[0083] Examples 1-10 are the synthesis of anion exchange COFs and their practical application in adsorbing the natural product glycyrrhetinic acid.
[0084] Embodiment 1: Synthesis of AECOF-42-BX (X = 0-100, X is the percentage of doping amount), taking the synthesis of AECOF-42-B50 as an example, the specific implementation steps are as follows: weigh 16.2 mg (0.1 mmol) of trimesaldehyde, 22.9 mg (0.075 mmol) of 2,5-bis(3-butene-1-oxy)terephthaloylhydrazide, and 28.4 mg (0.075 mmol) of 2-(2,5-di(hydrazinecarbonyl)phenoxy)-N,N,N-trimethylethane-1-ammonium bromide in a custom glass tube, add 1 mL of trimesaldehyde, 1 mL of 1,4-dioxane and 0.2 mL of 6 M acetic acid to the glass tube, freeze the mixture with liquid nitrogen and then evacuate it, repeat this operation three times, seal the tube with the flame of a hydrogen-oxygen generator, and place the glass tube in a 120 ° C oven for reaction for 3 days. After the reaction is completed, the product is transferred out, and the product is cleaned and activated for 24 h using a Soxhlet extractor with tetrahydrofuran as solvent, and then transferred to an 80 °C vacuum oven for drying. The treated product is subjected to characterization tests such as X-ray powder diffraction (PXRD), infrared (FT-IR), and nitrogen adsorption.
[0085] Embodiment 2: Characterization and analysis of AECOF-42-BX: The crystallinity and morphology of the cleaned and activated AECOF-42-BX were systematically characterized by X-ray powder diffraction (PXRD), infrared (FT-IR), nitrogen adsorption, transmission electron microscopy (TEM), scanning electron microscopy (SEM), etc. The characterization results are shown in Figure 3-7 .like Figure 3 The PXRD results show that materials with different doping ratios have characteristic peaks at 3.1° and 6.5°, which is consistent with the peak positions of the simulation data, indicating that they all have good crystallinity, indicating that the material synthesis is successful. Figure 4 In the infrared data, AECOF-42-BX has a wavelength of 1680 cm -1 The characteristic peaks of aldehyde group at 3320 cm -1 The amino characteristic peaks disappeared, while the peak at 1640 cm -1 There is an obvious imine bond peak at 1290-1305 cm -1 The characteristic absorption peak of quaternary ammonium group appears at , proving that quaternary ammonium salt monomer has been successfully incorporated. Figure 5 The nitrogen adsorption data showed that the specific surface area of the material gradually decreased with the increase of doping ratio, from about 793 m 2 / g drops to about 99 m 2 / g. The pore size remains basically unchanged at 1.8nm. Figure 6 and Figure 7 From the TEM and SEM fields of view, it can be seen that the material morphology changes significantly with the change of doping ratio. AECOF-42-B0 is spherical, and obvious vesicle structures appear in the fields of view of AECOF-42-B10-AECOF-42-B50, and the vesicle structures tend to increase gradually. As the doping ratio continues to increase, the vesicle structure gradually disappears, and the morphology of the material is an irregular block structure.
[0086] Embodiment 3: Selection of solvent for glycyrrhetinic acid adsorption: Dissolve 2 mg of glycyrrhetinic acid solid in 10 mL of anhydrous ethanol to prepare a 200 μg / mL glycyrrhetinic acid solution. Prepare different concentrations of NaOH solution (0.1 mM, 0.5 mM, 1 mM, 10 mM), Na2CO3 solution (0.1 mM, 0.5 mM, 1 mM, 10 mM), and NaHCO3 solution (1 mM, 2 mM, 3 mM, 4 mM, 5 mM, 10mM). Use these alkaline solutions to dilute the glycyrrhetinic acid solution to 20 μg / mL, add 40 mL of the above solution to 50 mL reagent bottles, and then add 5 mg AECOF-42-B50 to each bottle for adsorption. Take points at regular intervals, centrifuge to remove solid materials, and use a UV spectrophotometer to test the concentration of licorice in the supernatant to determine the adsorption amount of glycyrrhetinic acid by the material in different systems. Figure 8 In the NaOH solution and Na2CO3 solution systems, when the concentration is 0.1 mM, the material has a high adsorption capacity for glycyrrhetinic acid, which is 77 μg / mg and 67 μg / mg, respectively. When the concentration increases to 0.5 mM, the material's adsorption capacity for glycyrrhetinic acid rapidly decreases to below 20 μg / mg. As the concentration continues to increase, the adsorption capacity continues to decrease slightly. In the NaHCO3 solution, when the concentration is 1 mM, the adsorption capacity exceeds 80 μg / mg. As the concentration increases, the adsorption capacity also has a trend of gradually decreasing, but unlike in the NaOH solution and Na2CO3 solution, there is no sharp decrease in the adsorption capacity. Combined with the adsorption capacity of the material on glycyrrhetinic acid solution in different alkaline solutions and the solubility of different alkaline solutions on glycyrrhetinic acid, NaHCO3 solution is more suitable as an adsorption solvent for glycyrrhetinic acid.
[0087] Example 4 Adsorption experiment of glycyrrhetinic acid by COFs with different doping ratios: 20 μg / mL glycyrrhetinic acid solution was prepared using 1 mM NaHCO3 solution, and 5 mg of COFs with different doping ratios were added to 40 mL of the above solution for adsorption. The adsorption points were taken at regular intervals to calculate the adsorption amount of glycyrrhetinic acid by the material. Fig. 9As the doping ratio increases from 0 to 50%, the adsorption amount of glycyrrhetinic acid by the material gradually increases. As the doping ratio continues to increase, the adsorption amount gradually decreases.
[0088] Example 5 Adsorption experiment of glycyrrhetinic acid by AECOF-42-B50 under different pH conditions: Prepare 1mM NaHCO3 solution, and adjust the solution to different pH values using acetic acid and ammonia water. Prepare 20 μg / mL glycyrrhetinic acid solution using solutions of different pH values, add 5 mg AECOF-42-B50 to each system for adsorption, take points at regular intervals, and calculate the adsorption amount. Fig.10 As the solution pH increased from 3 to 7, the adsorption of glycyrrhetinic acid by the material gradually increased. As the pH continued to increase to 11, the adsorption showed a trend of gradually decreasing.
[0089] Example 6 Adsorption experiment of glycyrrhetinic acid by AECOF-42-B50 and different types of ion exchange resins: The ion exchange resins used for comparative experiments include D152 macroporous acrylic weak acid cation exchange resin, D301 macroporous weak base styrene anion exchange resin, D001 macroporous strong acid styrene cation exchange resin, chlorine-type strong base styrene anion exchange resin and HP-20 macroporous adsorption resin. 20 μg / mL glycyrrhetinic acid solution was prepared using 1mM NaHCO3 solution, and 5 mg of various resin materials were added to 40 mL of the above solution for adsorption. Points were taken at regular intervals to calculate the adsorption amount. Fig.11 The two cation exchange resins hardly adsorbed glycyrrhetinic acid, and the two anion exchange resins, neutral macroporous resin and AECOF-42-B50, had a certain adsorption effect on glycyrrhetinic acid. Within the adsorption time of 120 minutes, AECOF-42-B50 quickly reached adsorption equilibrium (20 minutes) and maintained the highest adsorption capacity; the two anion exchange resins reached equilibrium after 60 minutes of adsorption, while the neutral macroporous resin did not reach adsorption equilibrium after 120 minutes. From the above results, it can be concluded that AECOF-42-B50 has similar adsorption performance to anion exchange resins, with fast adsorption process and high adsorption capacity.
[0090] Example 7 Experiment on the effect of initial concentration of glycyrrhetinic acid on the adsorption capacity of materials: Glycyrrhetinic acid solutions of different concentrations (5 μg / mL, 10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL) were prepared using 1 mM NaHCO3 solution. 5 mg of AECOF-42-B50 was added to 40 mL of the above solution for adsorption, and points were taken at regular intervals to calculate the adsorption capacity. Fig.12As the initial concentration of glycyrrhetinic acid increased from 5 μg / mL to 20 μg / mL, the adsorption capacity of the material increased significantly; when the initial concentration continued to increase to 50 μg / mL, the adsorption capacity still increased, but the trend was not obvious.
[0091] Example 8 Selection of elution solvent after the material adsorbs glycyrrhetinic acid: Use 1 mM NaHCO3 solution to prepare a 20 μg / mL glycyrrhetinic acid solution, add 5 mg of AECOF-42-B50 to 40 mL of the above solution for adsorption. After 120 min of adsorption, collect the solid by centrifugation, and test the glycyrrhetinic acid concentration in the supernatant to determine the adsorption amount of glycyrrhetinic acid by the material. Prepare 10 mM NaHCO3 solution, NaOH solution, Na2CO3 solution, NaCl solution and NaBr solution, disperse the collected GA@AECOF-42-B50 adsorbed with glycyrrhetinic acid in 10 mL of the above solution for elution, take points at regular intervals, and test the glycyrrhetinic acid concentration in the supernatant. Fig.13 In the above solutions, the elution rate of glycyrrhetinic acid is very fast, and the desorption equilibrium can be reached within 5 minutes. In NaHCO3 solution, NaCl solution and NaBr solution, the single elution rate is about 40%; while in NaOH solution and Na2CO3 solution, the single elution rate is higher, more than 80%.
[0092] Example 9 AECOF-42-B50 recycling experiment: Add 5 mg of AECOF-42-B50 to 40 mL (20 μg / mL) glycyrrhetinic acid NaHCO3 solution (1mM) and adsorb for 120 min. Then collect the solid by centrifugation and test the glycyrrhetinic acid concentration in the supernatant to determine the adsorption amount of glycyrrhetinic acid by the material. Soak the collected solid in 10 mL Na2CO3 solution (10mM) for 30 min and desorb by centrifugation. Test the glycyrrhetinic acid content in the supernatant and repeat the desorption operation until no glycyrrhetinic acid is detected in the supernatant. Re-disperse the collected solid in the glycyrrhetinic acid solution for adsorption. Repeat the above adsorption-desorption operation 10 times. Fig.14 After 10 recycling experiments, the adsorption capacity of the material can still maintain more than 80% of the initial value.
[0093] Example 10 Adsorption experiment of glycyrrhetinic acid in fermentation broth: The specific steps include pretreatment of the fermentation broth and adsorption and separation of glycyrrhetinic acid in the fermentation broth after pretreatment.
[0094] Pre-treat the crude fermentation broth: extract the crude fermentation broth with ethyl acetate and water, collect the organic phase, remove the solvent and dissolve the residue in ethanol, add a large amount of Na2CO3 solution (50 mM-200 mM) to the above solution, and a large amount of solid will precipitate immediately. Filter to remove the precipitated solid impurities, collect the filtrate and remove the solvent, and redissolve the residue in ethanol for later use. Fig.15 After pretreatment, most of the impurities except glycyrrhetinic acid in the fermentation broth can be removed, and as the concentration of Na2CO3 solution increases, the impurities are removed more thoroughly. After pretreatment with 200 mM Na2CO3 solution, the purity of glycyrrhetinic acid reaches more than 70%.
[0095] Adsorption and separation of glycyrrhetinic acid in fermentation broth after pretreatment: Dilute the pretreated fermentation broth with 1 mM NaHCO3 solution, add AECOF-42-B50 to the glass bottle containing the above solution and place it on a shaker for adsorption. After the adsorption is completed, filter to separate the solid, add it back to the glass bottle, add 10 mM Na2CO3 solution to the bottle for elution, and after the elution is completed, filter and collect the material for subsequent reuse. Fig.16 After adsorption, the purity of glycyrrhizic acid can reach more than 99%.
Claims
1. A method for synthesizing an anion exchange covalent organic framework material, characterized in that The process comprises the following reaction steps: (1) adding organic monomer 1, organic monomer 2 and a solvent into a reactor and mixing them; (2) dissolving the organic monomer 3 in an aqueous solution of the catalyst and adding the solution into a reactor; (3) heating the reaction and separating the mixture to obtain the product; Wherein, the organic monomer 1 is a monomer containing an aldehyde group or an anhydride functional group, the organic monomer 2 is a monomer containing an amino group, a hydrazide or an acetonitrile functional group, and the organic monomer 3 is an amino group, a hydrazide or an acetonitrile functional group monomer having an ion exchange functional group in the side chain; the catalyst is a compound containing a carboxylic acid, anhydride, imidazole or hydroxyl functional group; The covalent organic framework material is a covalent organic framework material connected by vinyl, imide, imine, azine, keto-enol, hydrazone, β-ketoamine or triazine.
2. The synthesis method according to claim 1, characterized in that Organic monomer 1 is an aldehyde functional group compound with different connection forms (two, three, four connections); organic monomer 2 is an amino or hydrazide functional group compound with different connection forms; organic monomer 3 is a compound with ionic side chain functional groups of the same type and the same connection method as monomer 2.
3. The synthesis method according to claim 1, characterized in that The organic monomer 1 is terephthalaldehyde, 4,4'-biphenyldicarboxaldehyde, 1,4-di(4-formylphenyl)benzene, 1,3,5-tribenzaldehyde (TFp), 2-hydroxy-1,3,5-benzenetricarboxaldehyde, 2,6-dihydroxy-1,3,5-benzenetricarboxaldehyde, trialdehyde phloroglucinol (Tp), 1,3,5-tri(p-formylphenyl)benzene (TFPB), 2,4,6-tri(4-formylphenyl)-1,3,5-triazine (TFPT), 4,4',4''-[benzene-1,3,5-triyltri(acetylene-2,1-diyl)]tribenzaldehyde (TFEPB), 4,4',4''-(benzene-1,3,5-tri(acetylene-2,1-diyl))-tri(salicylaldehyde) , (2,4,6-tri-(4-formyl-biphenyl-4-yl)-1,3,5-triazine (TFBPT), tetra(4-formylphenyl)methane, 4,4',4'',4"'-silanetetraethyltetrabenzaldehyde, tetra(4-formylphenyl)ethylene, 1,3,5,7-tetraformyladamantane, 1,3,5,7-tetra(4-benzaldehyde)-adamantane; the monomer containing the aldehyde functional group can be optionally substituted by a substituent, and the substituent is selected from any one or more of -H, -OH, -NH2, -CN, -NO2, -OCH3, -SO3H, -CH3, -COOH, -COOCH3, -F, -Cl, -Br, -I. More preferably, the organic monomer 1 is 1,3,5-triformaldehyde (TFp) and 1,3,5-tri(p-formylphenyl)benzene (TFPB)' The organic monomer 2 is a monomer containing an amino functional group, which is hydrazine hydrate, p-phenylenediamine, benzidine, 1,3,5-triphenylamine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT), 4,4',4''-[benzene-1,3,5-triyltris(acetylene-2,1-diyl)]triphenylamine (TAEPB), 4',4''',4'''''-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)) (TABPB), 2,4,6-tris-(4-aminobiphenyl-4-yl)-1,3,5-triazine (TABPT), tetrakis(4-aminophenyl)methane, 4,4',4'' ,4"'-silanetetraethyltetraphenylamine, tetrakis-(4-aminophenyl)ethylene, 1,3,5,7-tetraaminoadamantane, 1,3,5,7-tetrakis(4-anilino)-adamantane; the monomer containing the amino functional group may be optionally substituted by a substituent, and the substituent is selected from any one or more of -H, -OH, -NH2, -CN, -NO2, -OCH3, -SO3H, -CH3, -COOH, -COOCH3, -F, -Cl, -Br, -I; the monomer containing the hydrazide functional group is optionally R-substituted terephthaloyl hydrazide; the R is , or , when multiple substitutions are present, each R is independently selected from the above structures. Further preferably, the organic monomer 2 is 2,5-bis(but-3-ene-1-oxy)terephthaloylhydrazide; The organic monomer 3 is a monomer containing an amino group or a hydrazide functional group, which is a monomer in which the substituent is replaced with any one or more of sulfonic acid (-SO3H), phosphoric acid (-PO3H2), carboxylic acid (COOH), phenolic hydroxyl (-OH), primary amine (-NH2), secondary amine (-NHCH3), tertiary amine [N-(CH3)2] and quaternary amine [-N(CH3)2] groups on the basis of organic monomer 2. More preferably, organic monomer 3 is 2-(2,5-di(hydrazinecarbonyl)phenoxy)-N,N,N-trimethylethane-1-ammonium bromide.
4. The synthesis method according to claim 1, characterized in that The catalyst is any one or more of acetic acid, scandium trifluoromethanesulfonate, benzoic anhydride, 4-trifluoromethylbenzoic anhydride, phenylacetic anhydride, acetic anhydride, trifluoroacetic anhydride, benzoic acid, 4-fluorobenzoic acid, 4-bromobenzoic acid, propionic acid, aromatic acid, imidazole, benzimidazole or phenol. More preferably, the catalyst used is acetic acid.
5. The synthesis method according to claim 1, characterized in that The reaction solvent is any one or more of methanol, ethanol, acetonitrile, mesitylene, o-dichlorobenzene, 1,4-dioxane, n-butanol, acetone, N,N-dimethylformamide, dimethyl sulfoxide, toluene, acetone, and tetrahydrofuran; preferably, the reaction solvent used is mesitylene and 1,4-dioxane, mesitylene and n-butanol, or o-dichlorobenzene and n-butanol.
6. The synthesis method according to claim 1, characterized in that The reaction temperature is 30°C-200°C, more preferably 60°C-150°C, most preferably 120°C.
7. The synthesis method according to claim 1, characterized in that The reaction time is 12 h-120 h, more preferably 48 h-96 h, most preferably 72 h.
8. An anion exchange covalent organic framework material prepared by the synthesis method of claims 1-7.
9. The covalent organic framework material according to claim 8, characterized in that The structural formula of the covalent organic framework material is as follows: , or , or .
10. Use of the covalent organic framework material according to claim 8-9, characterized in that: The covalent organic framework material is used for separation and purification of natural products.
Citation Information
Patent Citations
Mixed matrix anionic membrane and manufacturing method thereof
CN109546191A
Chiral separation membrane based on covalent organic framework material as well as preparation and application of chiral separation membrane
CN111318187A
Covalent organic framework material containing sulfonic acid groups as well as preparation and application of covalent organic framework material
CN112679731A
Carbon-carbon double bond bridging covalent organic framework material and preparation method thereof
CN112708090A
Trans-stacked covalent organic framework material as well as preparation method and application thereof
CN116425936A